Teopoetika: Sebuah Teologi yang Tidak Pantas - Tamawiwy, August Corneles (Indonesian Journal of Theology, 2024)
This article proposes theopoetics as an alternative to theology. It explores the distinction between ‘theo-poetics’ and ‘theo-poetry,’ elucidating the poetic (poiesis) aspects absent in theo-poetry. While theo-poetry employs theological language poetically and metaphorically, theo-poetics delves into poiesis as a reflection on the creation of meaning concerning the divine (theos), thereby supplanting logos in theo-logy. Theopoetics is not ‘negative theology’ but, as described by John D. Caputo, is a weak and radical theology. While strong theology actively seeks the highest episteme, theopoetics, being a weak theology, emphasizes a more passive and receptive mode. As a radical theology, theopoetics is a hovering spirit that haunts conventional theology, is not subservient to any institution or authority, and permeates down to its roots (radix). By uprooting logos in theo-logy, theopoetics emerges as a unique, though improper, theology.